2007
DOI: 10.1111/j.1532-5415.2007.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Completing an Advance Directive in the Primary Care Setting: What Do We Need for Success?

Abstract: The majority of studies demonstrated statistically significant effects associated with the advance directive intervention. The most successful interventions incorporated direct patient-healthcare professional interactions over multiple visits. Passive education of patients using written materials (without direct counseling) was a relatively ineffective method for increasing advance directive completion rates in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(243 citation statements)
references
References 30 publications
9
230
2
1
Order By: Relevance
“…Numerous approaches to sharing ACDs have been investigated both in Australia and internationally, but there has been limited universal uptake due to a lack of systematic processes for embedding them into routine practice at an institutional level and across health jurisdictions. 18 Furthermore, advance care planning needs to be normalised in all health settings. To date, the greatest hope for embedding ACDs across services and jurisdictions is the electronic medical record, which is an important facilitator of advance care planning.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous approaches to sharing ACDs have been investigated both in Australia and internationally, but there has been limited universal uptake due to a lack of systematic processes for embedding them into routine practice at an institutional level and across health jurisdictions. 18 Furthermore, advance care planning needs to be normalised in all health settings. To date, the greatest hope for embedding ACDs across services and jurisdictions is the electronic medical record, which is an important facilitator of advance care planning.…”
Section: Discussionmentioning
confidence: 99%
“…Linking the patient incentive with PCP encouragement may be helpful, because we found that a patient incentive combined with PCP encouragement was more powerful than either PCP encouragement or patient incentive alone. Future research should focus on strategies to overcome barriers to ACP-related best practice by PCPs, 27 experiment with alternative incentive designs (e.g., incentive size, target recipient), and engage different patient and provider populations.…”
Section: Discussionmentioning
confidence: 99%
“…For the providerdelivered patient incentive study, assuming an intra-class correlation of 0.05 26 and a rate of provider-reported ACP discussion of 10% in the control arm, we calculated that 20 PCPs per arm and 10 patients per PCP (n ¼ 200 per group) would provide 92% power at a two-sided alpha of 0.05 to detect a 15-percentage point absolute difference 27 between intervention and control groups. We used an intention-to-treat approach using generalized linear mixed models with a logit link and fixed effect for the intervention and practice type with a random effect for provider for the dichotomous outcomes.…”
Section: Study Design and Ethical Approvalmentioning
confidence: 99%
“…One group systematically reviewed studies designed to increase advance directive completion in primary care and identified a number of common themes in terms of barriers. 34 Physicians tended to blame 'lack of time', 'low health literacy of patients', 'lack of necessary skills', 'lack of privacy for discussion' and 'patients not sick enough' for lack of success in implementing ACP, while patients cited 'deferring decisions to physicians or family', 'inconsistency with religious beliefs', 'too distressing to discuss', 'documents too complicated' and 'plan to do it later'.…”
Section: Barriers To Acpmentioning
confidence: 99%
“…Primary care gives the opportunity for ACP to be an ongoing process, rather than a single event, with the potential for multiple appointments giving time for accurate assessment as well as true understanding to develop between patient and doctor. A systematic review of studies aimed at increasing completion of advance directives 34 found that the most successful interventions were those that incorporated direct patient-healthcare professional interaction over multiple visits.…”
Section: Why Primary Care?mentioning
confidence: 99%